2013
DOI: 10.1186/1752-153x-7-55
|View full text |Cite
|
Sign up to set email alerts
|

Multi-analyte approach for determining the extraction of tobacco constituents from pouched snus by consumers during use

Abstract: BackgroundSnus is a smokeless oral tobacco product with a significant history of use in Sweden, where it is regulated under food legislation. Users place a small porous sachet or a pinch of loose snus between the upper jaw and cheek for approximately one hour, leading to partial intake of tobacco constituents. To understand user exposure to tobacco, a multi-analyte approach based on the extraction of pouches by methanol, ethanol and water was validated and applied to the measurement of various constituents, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
(29 reference statements)
1
19
1
Order By: Relevance
“…21 A recent study revealed that the total TSNA level in an unused 1.000 g pouch of snus was approximately 0.830 µg/g, with quantifiable levels of NAT, NNK, NNN and NAB (0.268 µg/g, 0.191 µg/g, 0.344 µg/g and 0.025 µg/g, respectively). 33 Therefore, total TSNA levels in the Afzal sample analysed in the current study were fivefold higher than the recommended GOTHIATEK ® limits. Specific TSNA levels in Afzal were six-fold, 2.4-fold, 5.2-fold and 8.4-fold higher than the NAT, NNK, NNN and NAB levels, respectively, in snus.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…21 A recent study revealed that the total TSNA level in an unused 1.000 g pouch of snus was approximately 0.830 µg/g, with quantifiable levels of NAT, NNK, NNN and NAB (0.268 µg/g, 0.191 µg/g, 0.344 µg/g and 0.025 µg/g, respectively). 33 Therefore, total TSNA levels in the Afzal sample analysed in the current study were fivefold higher than the recommended GOTHIATEK ® limits. Specific TSNA levels in Afzal were six-fold, 2.4-fold, 5.2-fold and 8.4-fold higher than the NAT, NNK, NNN and NAB levels, respectively, in snus.…”
Section: Discussionmentioning
confidence: 51%
“…TSNAs are highly water-soluble; therefore, as the moisture content of a STP increases, the levels of soluble TSNAs may also rise, resulting in enhanced absorption by the oral mucosa. 33 The authors of the current study strongly believe that TSNAs are not safe at any level. As a result, it is strongly recommended that existing legislation in Oman regarding the illegal sale of Afzal be more strictly enforced.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…7,19 Higher nicotine levels are found in moist snuff in comparison to the dry form. 1 Additionally, it has been found that American moist snuff contains higher levels of NO 2 -and Cl -than the dry type.…”
Section: Discussionmentioning
confidence: 99%
“…2 The reported Cl -content in unused snus (35,300.00 µg/g) was close to that of Afzal as observed in the current study (33,170.80 µg/g). 19 Quantities of Swedish snus are well monitored as they are typically sold in 1.00 g tea bag-sized sachets; 19 in contrast, Afzal users usually self-determine doses (typically a pinch-sized amount per single dose ranging from 1.00-2.00 g) which are then repeated as desired. 13 As a result, Cl -consumption will increase due to repeated Afzal use during the day.…”
Section: Discussionmentioning
confidence: 99%